FACTORS THAT AFFECT THE AUDITORS’ INTENTION TO DO WHISTLEBLOWING IN SUPREME AUDIT INSTITUTION - Tanuwijaya, Hendry (Universitas Pamulang, 2020)
The high number of fraud that occurs makes many people doubt the performance of an auditor. Whistleblowing or the disclosure of fraud is believed more effective to overcome this phenomenon. This study aims to determine the effect of attitude toward behavior, subjective norm, perceived behavioral control, and personal cost of the auditor's intention to do the whistleblowing. The method of analysis used is multiple regressions analysis with the object of Supreme Audit Institution of Central Java. About 60 samples obtained from filling out the questionnaires, the result shows that attitude toward behavior and subjective has a positive effect on auditor’s intention to do the whistleblowing. However, perceived behavior control and personal cost have no effects auditors’ intention to do whistleblowing.